PENYULUHAN KESEHATAN: PENTINGNYA MELIBATKAN KELUARGA DALAM PERAWATAN HIPERTENSI - Sri Rahayu (Jurnal Abdimas Kesehatan (JAK), 2019)
Family involvement in family care becomes very essential. Refers to the patient's daily life, the family always accompanies the patient every day. Unfortunately, patients are less aware of family contributions in their care. Therefore, there is a need to make people aware of the importance the family care in hypertension cases. The targets are expected to increase the knowledge after health education and awareness of the importance the families in treating hypertension. Health education was used as a method. The results of this community service are expected to increase their knowledge and sensitize people with hypertension to involve the family in their care.